Artificial Intelligence: Deciphering the Links between Psychiatric Disorders and Neurodegenerative Disease - Stefano, George B; Büttiker, Pascal; Weissenberger, Simon; Esch, Tobias; Michaelsen, Maren M; Anders, Martin; Raboch, Jiri; Ptacek, Radek (Brain sciences, 2023)
Artificial Intelligence (AI), which is the general term used to describe technology that simulates human cognition [...].